Understanding hepatitis B, hepatitis C and HIV among people who inject drugs in South Africa: findings from a three-city cross-sectional survey - Andrew Scheibe; Katherine Young; Lorraine Moses; Rudolph L. Basson; Anna Versfeld; C. Wendy Spearman; Mark W. Sonderup; Nishi Prabdial-Sing; Jack Manamela; Adrian J. Puren; Kevin Rebe; Harry Hausler (BMC, 2019)
Abstract Background People who inject drugs (PWID) are at high risk for hepatitis C (HCV), hepatitis B (HBV) and HIV without accessible harm reduction programmes. Coverage of needle and syringe and opioid substitution therapy (OST) services in South Africa is below global recommendations and no hepatitis services exist for PWID. We assessed HCV, HBV and HIV prevalence and risk factors among PWID accessing harm reduction services in Cape Town, Durban and Pretoria to inform policy and programming. Methods We conducted a cross-sectional survey among PWID in these cities between August 2016 and October 2017. Participants were opportunistically sampled while accessing services. Study team members administered a questionnaire that assessed sociodemographic characteristics, drug use and sexual risk practices. We tested for HCV (antibody, viral load and genotype), HBV surface antigen (HBsAg) and HIV. Bivariate and multivariate analyses assessed associations with HCV serostatus. Results Nine hundred and forty-three PWID were included in the per protocol analysis. The majority (87%, 819/943) were male, the overall median age was 29 and most lived on the street (66%, 626/943). At last injection, 77% (722/943) reported using a new needle and syringe and 17% (163/943) shared equipment. HIV prevalence was 21% (196/926), HBsAg positivity 5% (47/936), HCV seroprevalence 55% (513/937), HCV viraemic prevalence (proportion tested with detectable HCV) 43% (404/937) and HCV viraemic rate (proportion HCV antibody positive with detectable HCV) 79% (404/513). HCV genotype 1a (73%, 270/368) was the most prevalent. In multivariate analysis, HCV infection was positively associated with residing in Pretoria (adjusted odds ratio (aOR) 1.27, 95% CI 1.21-1.34), living on the street (aOR 1.90, 95% CI 1.38-2.60), frequent injecting (aOR 1.58, 95% CI 1.15-2.16) and HIV infection (aOR 1.69, 95% CI 1.15-2.47), and negatively associated with black race (aOR 0.52, 95% CI 0.36-0.74) and sexual activity in the previous month (aOR 0.61, 95% CI 0.42-0.88). Conclusions HCV and HIV are major health threats affecting PWID in these cities. Access to OST and needle and syringe services needs to be increased and integrated with HCV services. Social and structural factors affecting PWID who live on the street need to be addressed.